Membangun Silogisme Pendekatan Naratif dalam Proses Pembuatan dan Analisis Kebijakan Publik William N. Dunn - Riedho, M. Roehman Zainur; Angga, I Made Prastika (Universitas Airlangga, 2024)
This research explains how to build a narrative approach syllogism in policy making and analysis using William N. Dunn's framework. The data used in this research uses secondary data from internet searches and literature from reputable journals. This research uses a qualitative and descriptive approach. The conclusion of this research is the syllogism of the narrative approach in public policy studies, consisting of the narrative approach in qualitative research methods, the narrative policy framework (NPF), and the advocacy coalition framework (ACF). In public policy studies, the activities of the policy-making process are divided into two actors with different tasks: first, policymakers carry out agenda setting, formulation, adoption, implementation, and evaluation of policies. Meanwhile, the second actor is a policy analyst, whose job is to identify problems, forecast policies, recommend policies, and monitor and evaluate policies. Each stage can use a narrative approach syllogism, where policymakers can explain and understand whether a policy will impact individuals or communities, understand the experiences and perspectives of the community or other stakeholders, build community empathy and support, and identify unexpected consequences. For policy analysts, the narrative approach of the syllogism is useful in terms of understanding the impact of policies, identifying emerging problems and conflicts, organizing and presenting policy recommendations clearly and persuasively, assisting with efforts to identify emerging issues, identifying dominant and alternative narratives that shape policy debates, understanding the formation, maintenance, and role of coalitions in the policy process, and evaluating policy effectiveness and adjusting recommendations. Keywords: Public policy, syllogism, narrative approach, Narrative Policy Framework (NPF), Advocacy Coalition Framework (ACF)